APPROXIMATION METHOD FOR DISCOVERY OF ANOMALOUS SIGNALS IN OPTICAL-ELECTRONIC DEVICES: APPROXIMATION METHOD FOR DISCOVERY OF ANOMALOUS SIGNALS IN OPTICAL-ELECTRONIC DEVICES - Stoyanov, Stiliyan (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The research is about registration of signals by optic-electronic devices. The subject of the current work is research of the approximative methods capability to discover anomalous signals in an impulse photometric device. The impulse photometric device ensures a high dimensional and timely resolution of the intensity distribution by natural optic emissions in the earth atmosphere and also light interference near the orbital station. The high spectral sensitivity and the dimensional resolution enable the research of fast processes, including pulsating polar lights, polar arcs, etc. When we discover and identify distant objects, the input informational signal is a continuous process with medium dispersion and correlation function. In the optic-electronic system the signal is a combination of equal values in time.